Macroeconomic effects of oil price fluctuations on emerging and developed economies in a model incorporating monetary variables - Farhad Taghizadeh-Hesary; Naoyuki Yoshino (Asian Development Bank Institute (ADBI), 2015)
The goal of this paper is to examine the impact of crude oil price movements on two macro variables, the gross domestic product (GDP) growth rate and the consumer price index (CPI) inflation rate, in three countries, the People's Republic of China (an emerging economy), Japan, and the United States (developed economies), in a model incorporating monetary variables (money supply and exchange rate). The main objective of this research is to investigate whether these economies are still reactive to oil price movements and compare their reactions. Monetary variables are included in this survey because our earlier research showed that they have a significant role in oil price determination. To assess the relationship between crude oil prices and macro variables we adopt an N-variable structural vector autoregression (SVAR) model. The results suggest that the impact of oil price fluctuations on developed oil importers' GDP growth is much milder than on the GDP growth of an emerging economy. On the other hand, however, the impact of oil price fluctuations on the People's Republic of China's inflation rate was found to be milder than in the two developed countries that were examined.
Keywords: Q43; E31; O57; 330; Oil; GDP growth rate; CPI inflation; developed economies; emerging economies